The Single image super resolution using Lifting-Based Directionlets - A P, Reji (INFOCOMP Journal of Computer Science, 2021)
This paper proposes, a fast learning based single image super resolution method which can be used for real time applications using multiple direction wavelet transform, called Directoionlets. Conventional directionlet transform is computationally very intensive, so a lifting based implementation is used here for super resolving both grey and colour images. Here two methods, directional variance method and skewed wavelet transform are used in implementing directionlet transform. From the results it is clear that directional variance method is faster than skewed wavelet method. Results using different wavelets like db4 ,bior3.3 etc are compared here. The simulation results showed that the proposed approach is faster and needs less memory compared to conventional directionlet based single image super resolution.